Hypertensive Patients Knowledge, Attitude and Practice for Stroke Prevention in Uttarakhand, India - Roshni Sinha; Poonam Verma; Kusum K Rohilla; C Vasantha Kalyani (Medsci Publications, 2020)
Introduction: Worldwide, Stroke becomes a public health problem. In India, reports indicating towards its emerging epidemic in near future. Hypertensive disease is considered as predisposing factor for Stroke. The present study aimed to assess knowledge, attitude and practice of hypertensive patients for stroke prevention in Uttarakhand, India. Methodology: The present study was a cross sectional study conducted on 243 hypertensive patients who were visiting outpatient department of All India Institute of Medical sciences (AIIMS), Rishikesh by using purposively sampling technique. Structured questionnaire of knowledge, attitude and practice were used to collect data from participants of the study. Data analysis was done by using SPSS version 23.0 statistical package. Results: Majority participants were of more than 60 years age, male, illiterate and no family history of hypertension. Most of participants were taking their regular treatment for hypertension. 185 (76%) hypertensive patients were having poor knowledge for stroke prevention. 215 (88%) participants had neutral attitude towards stroke prevention strategies whereas majority (64%) were following good practices. Conclusion: Findings suggested that policy makers should focus on health education of high risk group for stroke and also empower them with knowledge to control rising curve of stroke globally.